THE EPHEMERAL NATURE OF BEAUTY AND TIME IN CAVALIER POETRY - Eldorbek Erkin og’li Khamitov; Nurymbetova Zumrad Ruslanovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This  study  investigates  the  themes  of  transience,  temporal  beauty,  and  the fleeting  nature  of  life  in  Cavalier  poetry,  a  prominent  literary  movement  of  early seventeenth-century England. Poets such as Robert Herrick, Richard Lovelace, and Thomas Carew frequently emphasize the impermanence of youth, physical charm, and worldly  pleasures,  reflecting  the  cultural  and  philosophical  concerns  of  their  era. Through  detailed  analysis,  the  research  explores  how  carpe  diem  motifs,  striking imagery, and lyrical techniques convey the inevitability of aging and the urgency of embracing life’s fleeting joys. The study also considers the tension between moral conduct and indulgence in aesthetic and sensual pleasures, demonstrating the poets’ sophisticated  approach  to  human  desires  and  ethical  considerations.  By  comparing several works within the Cavalier tradition, the paper identifies recurring stylistic traits, including clarity of language, musicality, and rhetorical elegance, which enhance the poems’ emotional resonance and persuasive effect. Ultimately, this research shows that Cavalier poetry not only celebrates the pleasures of life but also meditates on mortality and  the  passage  of  time.  It  reflects  the  broader  social,  cultural,  and  philosophical currents  of  seventeenth-century  England,  making  it  a  valuable  resource  for understanding contemporary attitudes toward beauty, time, and human experience.